Gestão de protocolo: uma proposta teórica de novos modelos organizacionais - SANTOS, Felipe César Almeida dos (2022)
The present work had as main objective to demonstrate new organizational models for the accomplishment of protocol activities. Using the theoretical debates under protocol, centralization, decentralization, and deconcentration from the perspective of archaeology; Scoring the elements that support the importance of using the paradigms in the protocol and understanding how choosing a model will affect an organization's document management program. In addition, mentioning possible obstacles that may occur during the operation of each model studied. The research has an exploratory character and was developed through a bibliographical analysis involving the archival field and, simultaneously, the administrative area, as much of protocol, as of the centralized, decentralized and decentralized organizational models. In this way, the research presents the development of the concept of protocol, from its epistemology to contemporaneity, by becoming also an administrative unit, intrinsically linked to the documentary management of an institution. In addition, it elucidates about the selected organizational models, punctuating advantages and disadvantages in a possible application in a protocol sector. Coming to the conclusion of the need for a thorough analysis of the institution for the elaboration of management models.